Locative Constructions and Positional Verbs in Logba - Dorvlo, K. (Legon Journal of the Humanities, University of Ghana, 2011)
This article discusses the semantics of verbs which are used in basic locative constructions in Logba to code spatial information. I will show that there are twelve verbs in Logba, a Ghana Togo Mountain language. The verb le [‘be located’] is the unmarked form and eleven other positional verbs— kpɔ ‘lie’ kɔ ‘hang’ tɔ ‘fix’ tsi ‘ sit’ ye ‘stand’ gbɛ ‘lean’ gbo ‘ fall’ tsoga ‘lie across’ bata ‘wind round’ glɛ ‘tie’ dzi ‘tie firmly’— are used in three constructions in reply to a ‘where search’ question (see Dorvlo 2008). In the three constructions that will be presented, the subject NP position is filled by the Figure followed by the locative verb and the postpositional phrase (Ground). In the first construction, the unmarked locative verb is used and is followed by a postpositional phrase. The second construction is slightly different as the ground phrase is marked by a preposition while in the third construction the noun in the postpositional phrase can be analyzed as a body part noun. I will show that serial verb constructions involving two verbs are used to give an accurate description of the manner and position of the figure to the ground.